MORPHOLOGICAL AND BIOMETRICAL DESCRIPTION OF LINOGNATHUS STENOPSIS BURMEISTER, 1838ANDBOVICOLA CAPRAEGURLT, 1843FOUND IN GOATS - N. Nizamov (Trakia Journal of Sciences)
PURPOSE: The current studywas performed to present a morphological and biometrical description of the sucking louse Linognathus stenopsisBurmeister, 1838 (Anoplura: Linognathidae) and the chewing louse Bovicola capraeGurlt, 1843 (Ischnocera: Bovicolidae) found in goats. METHODS:A total of 100 male and 100 female lice of each species were subjected tomorphological and biometrical identification. The key points used for identification were as follows: head length (HL), head width (HW), thorax length (TL), thorax width at the prothorax (TW), abdomen length (AL), abdomen width (AW), total body length (TBL), index of the head (IH = HL/HW), index of the body (IB = TBL/AW), last segment length (LSL), last segment width (LSW) and index of the last segment (ILS=LSL/LSW) as well as the ratio of the total body length to the head length (TBL/HL). RESULTS:The complete morphological description of the species L. stenopsisrevealed that the TBLin females varies from 1.7 mm to 2.4 mm, while in males it ranges from 1.2 mm to 1.6 mm. The body length of female specimens of the species B. capraeranges between 1.5–1.9 mm, and that of males between 1.0–1.4 mm. TBL in L. stenopsisis strongly influenced by AL. The analysis shows a distinctive connection between TBLand AW as well as in AL and AW of females. TBL in female B. capraeshows a strong correlation with AW and AL and in males between TBL and AL and TL.CONCLUSIONS:These morphological and biometrical descriptions could be used as a reliable marker for species identification.